Exploring Character Development in Indonesian Students: A Qualitative Analysis of the Merdeka Curriculum in English Language Teaching (ELT) - hadijah; La Sunra; Syarifuddin Dollah (Linguistic, English Education and Art (LEEA) Journal, 2026)
The implementation of the Merdeka Curriculum in Indonesia has redefined the landscape of English Language Teaching (ELT) by emphasizing character development alongside linguistic competence. This study investigates how the curriculum promotes the six dimensions of the Pancasila Student Profile faith and noble character, global diversity, cooperation, independence, critical thinking, and creativity within ELT contexts at the secondary school level. Employing a qualitative design, data were collected through textbook analysis, classroom observations, and interviews with English teachers across three junior high schools in East Java. Content analysis was applied to examine how character values were integrated into ELT materials and classroom practices. The findings revealed that while noble character and cooperation were strongly emphasized in both textbooks and teacher practice, global diversity and critical thinking received limited attention. Teachers adapted activities to contextualize character values, yet constraints such as exam-oriented culture and limited teacher training hindered deeper integration. This study contributes to the growing literature on ELT and character education, highlighting the need for balanced representation of character dimensions. Implications are provided for policymakers, teachers, and material developers to enhance the holistic goals of the Merdeka Curriculum. Keywords: Character Development, ELT, Merdeka Curriculum, Pancasila Student Profile, Qualitative Study